Pengaruh Self Healing terhadap Penurunan Skala Nyeri Pasien Post Op - Ahmad Redho; Yani Sofiani; Anwar Wardi Warongan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to determine the effect of self-healing (healing touch) on reducing pain sensation for post-op patients at Tk II Kampar Regional Government Hospital, Bangkinang City. The method in this study used a quasi-experimental method with a pretest-postest design. The results of the bivariate analysis showed that there was a significant effect between self healing and pain scale in post op patients with p value <0.05. In conclusion, self-healing is used as one of the non-medicated methods to reduce the pain scale in post-op patients. Keywords: Post Op Patients, Self Healing, Pain Scale